Inventory and Identification of Arthropods on Dates (Phoenix dactylifera L.) - M. Indar Pramudi; Baserah Baserah; Helda Orbani Rosa (TROPICAL WETLAND JOURNAL, 2021)
Dates (Phoenix dactylifera L.) belong to the Arecaceae family of palms. Banjarbaru is one of the areas that started planting date palms in South Kalimantan. The community's knowledge of date pests still lacks. Therefore it becomes a problem for farmers. Before proper control is carried out, it is necessary to understand the types of pests first. Arthropod data on date palms at the Plantation and Livestock Service Office of South Kalimantan Province are not available. Hence, it is necessary to conduct inventory research and arthropod identification. This study aimed to determine the types of arthropods in date palms (P. dactylifera L.) in Banjarbaru. The method used was a survey method with purposive sampling carried out by collecting arthropods using swing nets, yellow sticky traps, and directly from four different locations. The field observations at four locations found 43 types of arthropods totaling 98 individuals. Twenty arthropods act as pests, 13 individuals as pollinators, and 10 individuals as predators. The arthropods were classified into ten orders and 27 families, with the largest number of individuals coming from the Lepidoptera order.